PENGARUH KUALITAS LAYANAN, NILAI PELANGGAN DAN LETAK GEOGRAFIS TERHADAP LOYALITAS PELANGGAN PADA VIA SALON TRENGGALEK - Rosyida, Sylvia Halimatur; Priantilianingtiasari, Ruly (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2023)
Growth in the hair care salon service industry in Indonesia own great potential to continue to grow, public awareness to care for hair is influenced by changes In the changing lifestyle of society and the new modern style that exists. improving services at hair care salon services, several factors are need a few things improving service quality, paying attention to customer value and maintaining geographichal location. This research aims to understand the effect of Service Quality, Customer Value and Geographical Location, on Customer Loyalty in Via Salon Trenggalek. The methodology used in this research uses is a quantitative approach with primary data obtained by filling out the Google form questionnaire. The population of this research is customers of Via Salon Trenggalek. There were a total of 70 respondents when taking samples using the Lemeshowâ€™s Â formula. This research uses SPSS 22 for data analysis, using multiple linear regression. The result of the research show that the variable Service Quality has no positive effect on Customer Loyalty, the customer value and geographical variables partially have a positive effect on customer loyalty on Via Salon Trenggalek. In addition, simultaneously service quality, customer value, and geographichal location affect customer loyalty at Via Salon Trenggalek.